Standing up against autocratization across political regimes: a comparative analysis of resistance actors and strategies. Issue 1 (2nd January 2023) - Tomini, Luca; Gibril, Suzan; Bochev, Venelin
ABSTRACT: Resistance against autocratization is a neglected area of inquiry. Although we have solid knowledge of the structural pre-conditions, modalities, and patterns of autocratization, as well as the motivations and strategies used by authoritarian actors, very little is known about the actors resisting autocratization and their strategies. This article provides an answer to the following questions: why does resistance against autocratization matter and why do we need to address it? How to define it? Who are the actors involved and what are the main strategies adopted? This article contributes to the current debate on autocratization by providing a detailed discussion on the topic of resistance and a definition that can be operationalized for empirical research. It also addresses this issue in a comparative perspective by analysing resistance against autocratization across different types of political regimes, therefore overcoming the narrow focus on democratic backsliding in democratic regimes. Eventually, based on the analysis of selected cases of successful resistance, we conclude by formulating working hypotheses to be further investigated on the density of resistance networks and the shifting nature of resistance when moving from democracy to authoritarianism.